This preview shows pages 1–3. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.View Full Document
Unformatted text preview: // p4 coend 4. Transform the expression shown in the first part of Problem 2 (p. 66) in the text book ( i.e. W, V, Y, and Z) using fork , join , and quit primitives. t1 = 2; t2 = 2; fork L1; fork L2; L1: W = X1 * X2; join t1,L3; quit; L2: V = X3 * X4; join t1,L3; quit; L3: fork L4; fork L5; L4: Y = V * X5; join t2,L6; quit; L5: Z = V * X6; join t2,L6; quit; L6: quit;...
View Full Document